Artificial Intelligence Governance in the Indonesian Business Sector under Ethical and Data Protection Challenges - Siti Syarifah Wafiqah Wardah; Yusi Irensi Seppa (Public Resource Innovation Management and Excellence, 2025)
The rapid adoption of Artificial Intelligence (AI) in the Indonesian business sector has reshaped operational efficiency while raising concerns regarding ethics and personal data protection. Grounded in theories of Responsible AI, algorithmic accountability, and data governance, this study aims to examine ethical and legal challenges arising from AI deployment, evaluate the adequacy of Indonesia’s regulatory framework, and propose a governance model suitable for business contexts. This research employs a normative juridical method supported by statute, conceptual, and comparative approaches. Data were analyzed qualitatively through interpretation and synthesis of legal norms, academic studies, and international frameworks such as the EU AI Act, OECD AI Principles, and ASEAN AI Governance Guidelines. The findings show that although AI enhances decision-making and automation in businesses, Indonesia lacks specific regulations on algorithmic transparency, risk-based AI classification, and corporate accountability. Existing laws, including the Personal Data Protection Law and the Electronic Information and Transactions Law, have not fully addressed these challenges. The novelty of this research lies in offering an integrated AI governance framework that combines ethical principles, data-protection standards, and corporate compliance to guide responsible AI implementation in Indonesian businesses. Keywords: Artificial Intelligence, responsible AI, data protection, corporate governance, ethical compliance